Optimal law enforcement and welfare in the presence of organized crime - Jenni Pääkkönen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
This paper explores the optimal law enforcement strategy of a Leviathan government in the presence of organized crime. The government is considered too weak to prevent an upsurge in crime, so it allows the mafia to generate a positive payoff by extracting rents in the shadow economy. From a strategic standpoint, the government, if it has the possibility to monitor shadow production and fine offenders, may not want to shut down illegal production or kick out the mafia, but instead can use its policing activity to capture additional revenue through fines on illegal firm activities and an increased tax base when mafia-harassed firms return to the legal sector. The option of escaping into the shadow economy can benefit some firms, even when this utility is diluted by the presence of a mafia. Monitoring hurts both legal and illegal firms, while the government benefits.
URN:NBN:fi:bof-201408072142
Keywords: H26; H41; K42; 330; organized crime; shadow economy; taxation